Behavioural Responses to Disability Insurance Generosity in a Work-Compatibility Setting - Francesca Zantomio; Michele Belloni; Vincenzo Carrieri; Elena Farina; Irene Simonetti (Institute of Labor Economics (IZA), 2024)
We investigate behavioral responses to the generosity of Disability Insurance (DI) within the context of work compatibility. Exploiting an institutional discontinuity leading to exogenous variation in replacement rates, we use rich administrative data on the work and health histories of Italian private sector workers and focus on individuals impacted by acute CVD shocks leading to unplanned hospitalizations. Using a Regression Discontinuity strategy, we identify a substantial DI response to benefit generosity, suggesting an elasticity of DI participation of 1.26. Additionally, we observe a smaller employment response, with an estimated elasticity of -0.15. Our findings indicate that the receipt of DI is widely perceived as a complement to labour income within a framework of work compatibility. These results carry significant implications for the design of labour-inclusive DI scheme.
Keywords: I38; J14; J22; H55; 330; disability insurance; elasticity; replacement rate; labour supply; regression discontinuity